PERCEPTION AND INTERESTS OF THE ADOLESCENT TO DIFFERENT QUESTIONS AND DECISION MAKING AS A SECONDARY STUDENT - Pérez López, Esteban (2019)
demanding and contemporary environment. It was investigated regarding their affinity and difficulty for the main subjects, the preferred modality to generate their knowledge, their affinity for the use of electronic devices, social networks and the Internet, their projection for the decision to pursue higher education, and others. The study was carried out in three different schools in the province of Alajuela (Grecia, Atenas, Pacto del Jocote) in Costa Rica. To capture the information, a consultation instrument (questionnaire) was designed, which was applied physically (on paper) to students at all levels of secondary school. The results obtained highlight that 64% of the adolescents included in the study consider Mathematics as the most difficult subject. 47% of adolescents chose the Science area as the subject they like the most. 58% of adolescents prefer assigning group work and exposing students as the most appropriate option for the teaching-learning process in the classroom. It also highlights that all respondents have a cell phone, 95% have internet on their cell phone, 94% of them use Facebook and 54% use WhatsApp. 81% of students are already clear that they would like to study in higher education. The main reason for choosing a career would be due to the affinity with the profession with 30%, followed by the good salary of the professional with 26%.